Why don't most merchants use price discounts to steer consumer payment choice? - Tamás Briglevics; Oz Shy (Federal Reserve Bank of Boston, 2012)
Recent legislation and court settlements in the United States allow merchants to use price discounts to steer customers to pay with means of payment that are less costly to merchants. This paper suggests one method of calculating merchants' change in profit associated with giving price discounts to buyers who pay with debit cards and cash. We use data from the pilot of the Boston Fed's Diary of Consumer Payment Choice to compute rough estimates of the expected net cost reduction by merchant type that may result from debit card and cash price discounts. We find that steering consumers to debit and cash via price discounts reduces some merchants' card costs. However, this cost reduction may be insufficient to offset the cost increase of administering price menus that vary by payment instrument. In addition, rewards buyers receive on credit card transactions may exceed the price discounts that merchants can provide. These factors may explain why steering via price discounts is not widely observed.
Keywords: E42; 330; steering payment methods; price discounts; card surcharges; merchant discount fee; swipe cost; payment instruments; payment methods